Microwave-assisted preparation of a silver nanoparticles/N-doped carbon dots nanocomposite and its application for catalytic reduction of rhodamine B, methyl red and 4-nitrophenol dyes. Issue 9 (28th January 2021) - G, Bhagavanth Reddy; Dadigala, Ramakrishna; Bandi, Rajkumar; Seku, Kondaiah; D, Koteswararao; Mangatayaru K, Girija; Shalan, Ahmed Esmail
Abstract : A silver nanoparticles/nitrogen-doped carbon dots (AgNPs/NCDs) nanocomposite was prepared by a microwave-assisted method, and exhibited high catalytic activity towards the reduction of rhodamine B, methyl red and 4-nitrophenol at ambient temperature. Abstract : In the current work, a silver nanoparticles/nitrogen-doped carbon dots (AgNPs/NCDs) nanocomposite was prepared by a microwave-assisted method that does not require additional reducing or stabilizing agents. Multiple analytical techniques were used to characterize the prepared nanocomposite. The nanocomposite exhibited a surface plasmon resonance (SPR) absorption peak at 420 nm, indicating the development of AgNPs with NCDs. Further, HRTEM results confirmed the formation of the nanocomposite with the appearance of lattice fringes of both materials. Additionally, the nanocomposite did not show any precipitation even after two months of storage. The nanocomposite exhibited high catalytic activity towards the reduction of rhodamine B (RhB, 98.83%), methyl red (MR, 97.14%) and 4-nitrophenol (4-NP, 99.95%) at ambient temperature. Besides, the kinetic analysis revealed that the reduction reaction followed pseudo-first-order kinetics and the calculated rate constants ( k ) for rhodamine B (RhB), methyl red (MR) and 4-nitrophenol (4-NP) were found to be 0.0296 s −1, 0.0233 s −1 and 0.029 s −1, respectively. Moreover, it is a reusable and stable catalyst for reduction reactions up to five cycles without significant loss in catalytic activity. Finally, a plausible mechanism for the reduction of pollutants is also discussed in detail. As a whole, the prepared nanocomposite might display stunning behaviour for wastewater treatment applications.